Geomagnetic signature of the 1999 August 11 total eclipse - Malin, SRC; Özcan, O; Tank, SB; Tunçer, MK; Yazici-Çakin, O (Blackwell Science Ltd, 2000)
The magnetic north (H), magnetic east (D) and vertically downward (Z) components of the geomagnetic field were monitored at Elazig, Turkey, with a three-component fluxgate magnetometer during the 1999 August 11 total eclipse of the Sun. The results were compared with those obtained with an identical instrument at Kandilli magnetic observatory, which is at a similar latitude to Elazig, but clear of the band of totality. An increase of D is found during the eclipse, rising to a maximum close to the time of maximum eclipse. The reality of this effect is confirmed by noting a similar feature, also centred on the time of eclipse, at a number of European observatories.
Keywords: eclipse; geomagnetism; ionosphere